2007
DOI: 10.1534/genetics.107.072637
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Whole-Genome Association Study of Efficient Food Conversion in Cattle

Abstract: The genetic factors that contribute to efficient food conversion are largely unknown. Several physiological systems are likely to be important, including basal metabolic rate, the generation of ATP, the regulation of growth and development, and the homeostatic control of body mass. Using whole-genome association, we found that DNA variants in or near proteins contributing to the background use of energy of the cell were 10 times as common as those affecting appetite and body-mass homeostasis. In addition, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
175
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 61 publications
5
175
2
5
Order By: Relevance
“…In beef cattle, some studies (Barendse et al, 2007;Nkrumah et al, 2007;) have reported associations between markers and RFI. For instance, Barendse et al (2007), using a commercial SNP chip containing approximately 10,000 (10K) SNP, analyzed 8,786 polymorphic SNP in 189 Australian beef cattle, chosen on the basis of being phenotypically high and low for RFI, and they detected 161 SNP associated with RFI at P < 0.01. Development of a commercial 50,000 (50K) SNP chip provided the opportunity to conduct a more powerful genomewide association study (GWAS) for RFI.…”
Section: Introductionmentioning
confidence: 99%
“…In beef cattle, some studies (Barendse et al, 2007;Nkrumah et al, 2007;) have reported associations between markers and RFI. For instance, Barendse et al (2007), using a commercial SNP chip containing approximately 10,000 (10K) SNP, analyzed 8,786 polymorphic SNP in 189 Australian beef cattle, chosen on the basis of being phenotypically high and low for RFI, and they detected 161 SNP associated with RFI at P < 0.01. Development of a commercial 50,000 (50K) SNP chip provided the opportunity to conduct a more powerful genomewide association study (GWAS) for RFI.…”
Section: Introductionmentioning
confidence: 99%
“…A direct result of the bovine genome sequencing has been the construction of arrays consisting of tens of thousands of SNP that can be genotyped in parallel (Matukumalli et al 2009; The Bovine HapMap Consortium 2009), which could be used for the practical purpose of identifying quantitative trait loci (Geldermann 1975;Barendse et al 2007) as well as of implementing genomic selection (Goddard and Hayes 2007). Other usages include the estimation of pairwise relatedness between individuals in the absence of pedigree data (Oliehoek et al 2006;Lee et al 2010) and high resolution studies of breed relationships and diversity (Pritchard et al 2000;Patterson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This assertion has been recently confirmed by two molecular studies in which allele substitution effects at several SNP loci distributed across the bovine genome were shown to be associated with RFI and FCR in B. taurus cattle (Barendse et al, 2007;Sherman et al, 2008).…”
Section: Snp Validation In Candidate Bovine Imprinted Genesmentioning
confidence: 64%